2018
DOI: 10.1007/s11920-018-0927-6
|View full text |Cite
|
Sign up to set email alerts
|

Mind-Body Therapies in Childhood Cancer

Abstract: Current data suggests that MBTs have been effective in decreasing symptoms related to oncologic pathology in children. Based on experience in our institution, the administration of these therapies can be expanded with the use of technology and also foster family inclusion in care, which can lead to improved quality of life for the patient and family. Further studies are warranted to ascertain the effects of MBTs in childhood cancer. MBTs are increasingly important in the care of youth with oncologic disease. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 87 publications
0
4
0
4
Order By: Relevance
“…A number of mostly small studies, including the current study, have examined various complementary therapies including Reiki, massage, music, hypnosis, parental coaching, and other mind–body techniques for symptom management in children with cancer. These studies consistently found improvement in symptoms and more than one mentioned increased parent–child bonding (Friedrichsdorf & Kohen, 2018; Genik et al, 2020; O’Callaghan et al, 2011; Thrane, 2013; Velez-Florez et al, 2018; Zucchetti et al, 2019). These results are encouraging for the use of complementary therapies for symptom management for children and adolescents with cancer.…”
Section: Implications For Children With Cancermentioning
confidence: 84%
“…A number of mostly small studies, including the current study, have examined various complementary therapies including Reiki, massage, music, hypnosis, parental coaching, and other mind–body techniques for symptom management in children with cancer. These studies consistently found improvement in symptoms and more than one mentioned increased parent–child bonding (Friedrichsdorf & Kohen, 2018; Genik et al, 2020; O’Callaghan et al, 2011; Thrane, 2013; Velez-Florez et al, 2018; Zucchetti et al, 2019). These results are encouraging for the use of complementary therapies for symptom management for children and adolescents with cancer.…”
Section: Implications For Children With Cancermentioning
confidence: 84%
“…Literatürde, kanser tedavisi alan çocuklarda hipnoz yönteminin kullanılmasıyla ilgili sınırlı sayıda çalışmaya rastlanmıştır. Hipnoz çocuklarda bulantı-kusmanın tedavisinde kullanıldığında olumlu sonuçlar elde edilmiştir [5,46]. Yapılan iki çalışmada; kemoterapiye bağlı gelişen beklentisel ve gecikmiş bulantı- kullanılabileceği belirtilmektedir [5].…”
Section: Masajunclassified
“…Hipnoz çocuklarda bulantı-kusmanın tedavisinde kullanıldığında olumlu sonuçlar elde edilmiştir [5,46]. Yapılan iki çalışmada; kemoterapiye bağlı gelişen beklentisel ve gecikmiş bulantı- kullanılabileceği belirtilmektedir [5].…”
Section: Masajunclassified
See 2 more Smart Citations